Conceptual analysis of foreign trade in Mexico (food sector) (Revista de Investigaciones Universidad del Quindío, 2023)
Trade is an essential part for economic development both locally, nationally as well as globally through the exchange of goods and services between different actors. It is an integral part of the global economy and plays a crucial role in the economic development of countries. Trade also presents challenges and problems, such as trade imbalances, unfair competition, trade barriers, environmental and social impacts, among others. That's why many countries negotiate trade agreements and establish regulations to facilitate fair and equitable trade. That is why this research is carried out to know how foreign trade develops within Mexico and the impact it generates on its economy, this will be carried out through a descriptive methodology with which it seeks to have a more appropriate approach around the objective of this work that is to be able to analyze foreign trade around Mexico, where it could be concluded that Mexico is an important country within the foreign trade environment both in its imports and exports, having an efficient and global economy.
Keywords: foreign trade; economy; export; import